Kinematic features of dipole photomotors - Korochkova, T. Ye.; Dekhtyar, M. L.; Rozenbaum, V. M. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2008)
The kinematic characteristics of a dipole photomotor have been studied in relation to its molecular structure and the parameters of the photoexcitation source. As found, the velocity of dipole photomotors is of the same order of magnitude as that of typical protein motors, and its sign and magnitude are controllable by varying the relative durations of laser pulses and dipole moment magnitudes of molecules.